Higher education policy in the EU, an institutional account - Tzortzis, Konstantinos (2008)
This research examines the development of the EU higher education policy under the theoretical lenses of historical institutionalism. Starting from the assumption that institutions matter, this thesis follows the evolution of higher education policy in the EU premises from its emergence in the early 1970s to date. Unfolding in four phases, this case study focuses on the institutional parameters of the policy and the polity context in order to explain the critical factors that shaped the policy outcomes and the scope of higher education. In a story development full of unanticipated consequences and normative building, this thesis critically examines the relation between the levels of governance to assess their impact on the policy outcome.